Penerapan SLiMS (Senayan Liberry management) untuk Meningkatkan layanan di Perpustakaan SMPN 2 Kabuh - Jauhari, Mohamad Imam; Masrur, Mukhamad; Fibrian, Ivan Dwi (Lembaga Dongan Dosen, 2025)
SMPN 2 Kabuh is a formal educational institution that organizes a 9-year compulsory education program in accordance with the National Education Law No. 2/1989. One of the supporting facilities for learning in schools is a library that functions as a learning resource with three main functions: collecting, storing, and presenting information. To support these three functions, a management system is needed that is able to improve services to be more efficient, fast, and precise. This research was conducted at the SMPN 2 Kabuh library using an interview method with library officers to obtain data related to the system used. The results of the analysis show that the system currently implemented is still manual-based, so it requires the development of a library information system. The researcher proposed and implemented an information system to stop library operations and improve service quality. The results of the User Acceptance Testing (UAT) test, which involved the head of the library and the manager, showed good and acceptable results. However, several shortcomings were still found, especially in the exploration of system features. Further adjustments are needed to ensure that the system can function optimally and completely replace the manual methods used previously.